PENGARUH MEKANISME CORPORATE GOVERNANCE DAN CASH HOLDING TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA - Ade Riandar Putra, Syarifah Rakhmawati (Departemen Manajemen, 2016)
This study aimed to examine the effect of Mechanism Corporate Governance and Cash Holding on Firm Value. The Independent variables in this reseacrh are the board commissioner, board independent, insider ownership, and cash holding, for the dependent variable is firm value that proxied by Tobins Q. This study use data of 37 companies manufactur in the Indonesian Stock Exchange for the periode 2010 until 2014. The sampling method used in this study was purposive sampling , is sampling based criteria. The analysis technique used in this study using multiple regression analysis with using program SPSS 21. The result showed that: (1) board commissioner and board independent have positive effect and significat on firm value, (2) insider ownership have negative effect and doesnt significant on firm value, (3) cash holding have positive effect and significant on firm value. The results of this study are expected to be taken into consideration for the company in decision making related to the implementation of good corporate governance and cash holding so as to enhance shareholder value. Kata Kunci: Dewan Komisaris, Komisaris Independen, Kepemilikan Manajerial, Cash Holding, Nilai Perusahaan